STUDI TERHADAP UNJUK KERJA PEMBANGKIT LISTRIK TENAGA SURYA ATAP KANTOR DESA PADANGSAMBIAN KAJA - Baskara Formasakti; I Nyoman Setiawan; Ida Ayu Dwi Giriantari (Program Studi Teknik Elektro UNUD, 2021)
The Padangsambian Kaja Village Government in Denpasar City through the SDGsprogram from the Ministry of Villages, Development of Disadvantaged Regions andTransmigration has implemented clean and renewable energy. The power plant being operatedis the rooftop solar power plant with a capacity of 7,2 kWp which is connected to the PLNnetwork. The study was conducted to determine the performance of the installed solar powerplant with the help of HelioScope software simulation. Energy production will be comparedbetween the simulation results of the 2 scenarios with the results of monitoring on the inverter inthe period from May to July 2021, so that it will be known the factors that influence theproduction of solar power plant energy. The results show the potential for energy productioneach year from the simulation results of scenario 1 and scenario 2 respectively are 9.964 kWhand 10.306 kWh, and the simulation results for energy production in the period from May to Julyin scenario 1 and scenario 2 respectively are 2.937,3 kWh and 3.057,8 kWh. Energy productionfrom scenario 1 and scenario 2 simulation is higher than real energy production, with adifference of 180,9 kWh with a percentage of 6,1% for scenario 1, and 301,4 kWh with apercentage of 9,8% for scenario 2.